Ontological CFD-repository - V. A. Zenkin (Труды Института системного программирования РАН, 2018)
Based on the RDF-storage, a software tool was developed for creating a knowledge base containing information about the CFD-calculations performed. The software is a set of scripts written in bash and python, which are published under the GNU GPL3 license. The tool is designed to support the user when making research studies that do not have a strict, pre-defined design of experiment or problem solving algorithm. To formalize the description of the calculation stored in the knowledge base, an ontology is created that serves as the information model for the calculation. As an auxiliary mechanism for carrying out an automated comparison of calculations with each other (a mechanism of "comparators" and "features") was developed and also described in the article. In addition to the systematized data storage, the complex provides the possibility of their automated and semi-automated analysis, including the presentation of a set of calculations in the form of an undirected graph, the construction of flat and spatial dependencies, the search for similar calculations, etc. The article gives examples of data processing results for the project on design of channel in the cylinder head of a piston engine.